Tree influence exacerbates the El Niño effects over soil CO2 emissions and its microclimatic controls - Salazar Zarzosa P. (2020)
Dryland ecosystems are considered the largest global carbon sink. However, extreme climate phenomena like the El Niño events (EN) may change soil respiration (Rs) – the CO2 emitted from soils resulting from biological activity and the largest outgoing flux of carbon from terrestrial ecosystems. Our aim was to study the effect of the EN on Rs in the North Peruvian dryland forest, and its interaction with soil temperature and the tree canopy. Our results indicate that Rs during the EN years increased by a factor of 100 compared to normal years, but this effect was exacerbated by the proximity to trees. Only under trees and during the EN event temperature exerted a positive control over daily Rs fluctuations. Our results, indicate how in these dryland forests the expected increase in the EN frequency and intensity could affect soil CO2 emissions, and hence ecosystem carbon budgets, but that this effect would very much depend on tree density and tree spatial distribution. © 2019 Elsevier B.V.